2018
DOI: 10.18203/issn.2454-5929.ijohns20183398
|View full text |Cite
|
Sign up to set email alerts
|

Etiopathological study of pediatric neck masses in a rural population

Abstract: <p class="abstract"><strong>Background:</strong> Neck mass in pediatric age group is a common clinical condition encountered by an ENT Specialist. Detailed clinical examination and knowledge of the common neck masses in children, which differ from those in adults is vital in early diagnosis and treatment. Diagnostic modalities such as Ultrasonography, Computerised Tomography, Fine needle aspiration cytology (FNAC) and histopathological examination aids in the diagnosis of superficial neck mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Commonest head and neck cystic lesions were benign congenital cysts and inflammatory lesions mainly hot and cold abscess, Z N Stain were shows positivity in 62% cases of cold abscess. Similarly, Sharrif et al reported the inflammatory lesions accounting for 64%, followed by the congenital 20% [13]. In rest patients has already started AKT by some family physician without confirming the diagnosis.…”
Section: Original Research Articlementioning
confidence: 88%
See 2 more Smart Citations
“…Commonest head and neck cystic lesions were benign congenital cysts and inflammatory lesions mainly hot and cold abscess, Z N Stain were shows positivity in 62% cases of cold abscess. Similarly, Sharrif et al reported the inflammatory lesions accounting for 64%, followed by the congenital 20% [13]. In rest patients has already started AKT by some family physician without confirming the diagnosis.…”
Section: Original Research Articlementioning
confidence: 88%
“…The lesion in the neck is visible to the patient and others and can be a source of constant worry to the patient and parents. For a clinician, a neck lesion could be a sign of deep seated pathology which nobody can afford to overlook [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation